Ruta montana (L.) L.: An insight into its medicinal value, phytochemistry, biological properties, and toxicity - Nesrine Benkhaira; Saad Ibnsouda Koraichi; Kawtar Fikri-Benbrahim (Shahrekord University of Medical Sciences, 2022)
Ruta montana (RM) is a medicinal and aromatic plant (MAP) used in folk medicine, especially in North Africa, to treat digestive, infectious, respiratory, neurological, gynecological, and diabetic diseases. The current work aims to review the scientifically validated ethno-medicinal usage, bioactivities and phytochemistry of RM, in order to provide data support for further investigations. Data were procured from PubMed, Scopus, Google Scholar, Web of Science, ScienceDirect, and PubChem. The present study revealed that RM could be used to manage many diseases involved in public health problems, such as diabetes, hypertension, neurological disorders, infections, reproductive system disorders, and cancer. It might also replace chemical insecticides and fungicides since it exhibits antifungal, insecticidal, and larvicidal properties. RM extracts also contain mainly coumarins and alkaloids. The volatile oil of RM is characterized by an abundance of ketone compounds and 2-undecanone as major constituents. In the case of a high-dose administration, RM infusion can cause poisoning through the oral path. Thus, in-depth in vivo pharmacological studies and clinical trials are needed to transmute the traditional applications of RM into scientific-based information.